2018
DOI: 10.1007/s12550-018-0336-z
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the mycotoxin metabolite dihydrocitrinone with serum albumin

Abstract: Citrinin (CIT) is a nephrotoxic mycotoxin produced by Penicillium, Monascus, and Aspergillus species. CIT appears as a contaminant in cereals, cereal-based products, fruits, nuts, and spices. During the biotransformation of CIT, its major urinary metabolite dihydrocitrinone (DHC) is formed. Albumin interacts with several compounds (including mycotoxins) affecting their tissue distribution and elimination. CIT-albumin interaction is known; however, the complex formation of DHC with albumin has not been reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…For a reversible process of chromatographic analysis, the dissociation of the analyte and buffer and the solute migration during retention, which could be affected by the column temperature change, are applicable to the Van't Hoff equation (Faisal et al, 2018;Marchetti et al, 2019;Yuan et al, 2020) as follows:…”
Section: Influence Of Temperaturementioning
confidence: 99%
“…For a reversible process of chromatographic analysis, the dissociation of the analyte and buffer and the solute migration during retention, which could be affected by the column temperature change, are applicable to the Van't Hoff equation (Faisal et al, 2018;Marchetti et al, 2019;Yuan et al, 2020) as follows:…”
Section: Influence Of Temperaturementioning
confidence: 99%
“…Following the biotransformation of CIT, the main metabolite formed appearing in the human urine is dihydrocitrinone (DH-CIT) [ 21 , 22 ]. The toxicity of DH-CIT was investigated, and the studies revealed that its cytotoxic potency was clearly lower compared with CIT as well as its genotoxic potential [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…After oral exposure, CIT is extensively metabolized and its main urinary metabolite dihydrocitrinone (DHC; Figure 1) is formed [5,6]. Because DHC is a less toxic compound than CIT, it is a detoxification process [7,8]. Based on previous reports, DHC appears in detectable quantities in human blood and urine samples [6,9,10,11].…”
Section: Introductionmentioning
confidence: 99%